Peningkatan Literasi Keuangan Digital Bagi Generasi Z di Kota Pare-Pare: Peran Serta PT Telkom Sto Kota Pare-Pare - Nuraini; Pratiwi, Ardita (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
In this era of the industrial revolution 4.0, access to information can be received directly from anywhere and anytime through the use of the internet.From year to year, internet usage has increased, especially in the use of social media by most of the younger generation.Therefore,it is necessary to strengthen the abilities and skills of the younger generation in digesting the information obtained. In this case, digital literacy plays a very important role in changing analytical and critical mindsets in receiving existing information.This community service activity is in the form of counseling/providing material related to strengthening digital literacy online and offline.The method of this activity includes problem identification, planning, preparation, counseling/delivery of material and evaluation.The results of this study are an increase in understanding of digital literacy through the participation of PT Telkom STO in the city of PARE-PARE. Based on the research that has been carried out,it provides a positive response for the younger generation in the form of a very good level of understanding,namely more than 50% of online and offline participants really understand the material presented